Postharvest handling of "etrog" citron (Citrus medica, L.) fruit. Issue 1 (2nd January 2016) - Klein, Joshua D.; Raz Shalev, Yonit; Cohen, Shlomo; Fallik, Elazar
ABSTRACT: Citron ( Citrus medica, L.) fruits ("etrog" in Hebrew; plural "etrogim") are used ritually in the Jewish holiday of Sukkot (Tabernacles), and can command as much as US$100/fruit, depending on quality. The etrog is unique among citrus fruits in that only the external attributes are of commercial importance. Maintaining physical fruit quality mandates the use of protective cushioning on the tree, at harvest, and in packaging. Growers use a wide range of chemical treatments post-harvest to reduce to a minimum the possibility of disfiguring insect or disease infestations. Most etrog varieties are highly susceptible to chilling injury if stored at less than 12°C. Etrogim lose water readily during storage, so fruit are stored and almost always marketed in plastic bags that limit water loss. Skin color is regulated with applications of ethylene or gibberellin, depending on whether specific markets prefer fruit that are greener or more yellow.